Aid and Fiscal Management - Lane, Timothy (IMF Working Papers; Working Paper, 2002)
This paper focuses on the macroeconomic aspects of fiscal management in aid-receiving countries. Despite the declining share of aid in budgets of donor countries, aid continues to play an important role in many developing countries. The paper first discusses the implications of aid in the economy as a whole and highlights the possibility of Dutch-disease effects of aid. Second, it discusses the implications of aid for short-term fiscal policy management?in particular, how actual or anticipated changes in aid receipts should be reflected in government spending.